Lead Acetate Induced Nephrotoxicity In Wistar Albino Rats. A Pathological, Immunohistochemical And Ultrasructural Studies - K.SUJATHA,; CH.SRILATHA,; Y.ANJANEYULU,; P.AMARAVATHI, (International Journal of Pharma and Bio Sciences, 2011)
Lead is a long – known poison of environment and industrial origin. Prolonged exposure damage cellular material and alters cellular genetics and produces oxidative damage. In the present study rats were treated with different doses of lead acetate (60 mgs and 30 mgs / Kg.b.wt. / 3days a week respectively) over a period of 12 weeks and biochemical, oxidative stress, gross & histopathological changes, histochemistry, immunohistochemistry and ultrastructural changes were studied in kidney. Increased serum creatinine levels and decreased antioxidant enzymes (CAT, SOD & GPx) activity in lead treated animals. Histopathologically dose dependent changes were observed in kidneys and revealed severe degenerative changes, intertubular haemorrhages, atrophied and cystic glomeruli were observed in majority of higher doses of lead treated rats. Alkaline phosphatase activity was more in the treated groups of kidney. The number of apoptotic bodies in kidney diffusely increased in PCT epithelium against BAX and BCl2 markers. However, the altered creatinine and enzymatic, histopathological, histochemical, apoptotic bodies and ultrastrucural changes are dose dependent in the present investigation.